2008
DOI: 10.1245/s10434-007-9747-3
|View full text |Cite
|
Sign up to set email alerts
|

The National Cancer Data Base: A Powerful Initiative to Improve Cancer Care in the United States

Abstract: The National Cancer Data Base (NCDB) is a nationwide oncology outcomes database that currently collects information on approximately 70% of all new invasive cancer diagnoses in the United States each year and serves as a powerful clinical surveillance and quality improvement mechanism for cancer programs participating in the American College of Surgeons (ACoS) Commission on Cancer (CoC) approvals program.1-3 Currently, the NCDB receives over one million cancer case reports annually from more than 1,430 hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1,183
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 1,674 publications
(1,194 citation statements)
references
References 36 publications
6
1,183
4
1
Order By: Relevance
“…The NCDB increased data quality-assurance measures starting in 2002. 18 Our findings is consistent with a more recent report from the SEER database by Mendelsohn et al in which they analyzed data of 22,724 patients with papillary thyroid cancer (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001). They demonstrated that there is no survival difference between lobectomy and total thyroidectomy.…”
Section: Discussionsupporting
confidence: 93%
“…The NCDB increased data quality-assurance measures starting in 2002. 18 Our findings is consistent with a more recent report from the SEER database by Mendelsohn et al in which they analyzed data of 22,724 patients with papillary thyroid cancer (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001). They demonstrated that there is no survival difference between lobectomy and total thyroidectomy.…”
Section: Discussionsupporting
confidence: 93%
“…Data from the NCDB represent 1,500 Commission on Cancer-accredited facilities including more than 70% of all newly diagnosed cancer cases in the United States. These data are used to track treatments and outcomes as well as provide qualityrelated performance measures [10].…”
Section: Methodsmentioning
confidence: 99%
“…This approach avoids potential pitfalls of highly curated specialty or institutional databases that may provide granular data but are limited by institutional and referral biases that may limit the generalizability of their findings [10,18].…”
Section: Commentmentioning
confidence: 99%
“…13 The more than 1450 hospitals approved by the Commission on Cancer are required to report all new cancer diagnoses to the NCDB. These hospitals report approximately 1 million new cancer cases to the NCDB each year, which account for approximately 70% of all cancers diagnosed in the United States annually.…”
Section: Data Source and Study Populationmentioning
confidence: 99%